STRATEGIC MANAGEMENT PRACTICES AND THEIR IMPACT ON ORGANIZATIONAL PERFORMANCE: A COMPARATIVE STUDY OF STARTUPS AND ESTABLISHED FIRMS - Talwekar, Ajay (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study focuses on strategic management as adopted by startups and established companies and the influence of the adopted management on the organizations. As business ecosystems and the competitive market shortly develop, strategic decisions are critical in identifying the success and survival of organizations. The paper applies the use of a comparative paradigm to evaluate the difference and similarity in strategic planning, implementation and assessment of startups and mature firms. The information was gathered by means of regularized surveys and interviews in different industries. The results demonstrate that despite the high dependence of an established company on a long-term and systematic strategic preparation, with startups, freedom, creativity and rapidity play an important role. Nevertheless, the two models are different when it comes to influencing performance. The research ends with some findings that would assist the two kinds of companies in improving their approaches.